Linkages of Technical Vocational Education and Training to Employment in Nepal (Research Nepal Journal of Development Studies, 2019)
Technical Vocational Education and Training (TVET) contribute to human resources development. The job market can be enhanced through it that can enable youth to enter into the workforce, cope with unemployment problem and contribute to the nation development. TVET can only do this if the graduates could meet the market demand. On the above background and within the framework of qualitative research methodology, this paper reviews the information of the written documents related with TVET development in Nepal. The paper concludes that TVET should create new opportunities for students and the market requirement should attract skillful students. It also requires bringing systematic changes in TVET according to the changed values of society. For the success of TVET, it needs to ensure that young people are equipped with social and market-related skills so that they can easily enter into the job market.